1883 Wash. Sess. Laws 139-40, An Act to Incorporate the City of Whatcom, ch. 2, § 8. - (:unkn) unknown (My University, 1883)
The city of Whatcom shall have the power to prevent injury or annoyance from anything dangerous, offensive, or unhealthy . . . to regulate and prohibit the carrying of deadly weapons in a concealed manner; to regulate and prohibit the use of guns, pistols and firearms, fire-crackers, bombs and detonating works of all descriptions[.]
Keywords: CARRY - CONCEALED; DISCHARGE